2019
DOI: 10.1007/s10344-019-1275-5
|View full text |Cite
|
Sign up to set email alerts
|

Lynx eats cat: disease risk assessment during an Iberian lynx intraguild predation

Abstract: Lethal interactions between members of the carnivore guild are well represented in literature. In the Iberian lynx, interspecific killing (without prey consumption) of some mesocarnivores, such as the Egyptian mongoose, genet, and red fox, has been reported. Although vaguely documented, evidence suggests feral cats fall victim to interactions with this apex predator. Here, we describe the first documented case of interspecific killing and partial consumption of a feral cat by an adult male Iberian lynx reintro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Millán and Casanova [ 17 ] found an overall higher parasite prevalence in feral cat samples (84%) than in Iberian lynx samples and several parasites that both felines share, which means that domestic/feral and wild cats may be an important reservoir of parasites that can affect the Iberian lynx. In fact, Nájera et al [ 35 ] reported, for the same population in study, a case of interspecific killing and partial consumption of a feral cat by an Iberian lynx individual, which evidence the disease risk and possible outbreak that this domestic/feral species can represent for the Iberian lynx, especially in small/newly reintroduced populations. With the exception of T. cati , which is more cat-specific, according to Ribas et al [ 36 ] and Olmedo et al [ 37 ], most of the parasites found in this study have low host specificity and have mutual wild carnivores’ families, which can be explained by their similar generalist diet composition.…”
Section: Discussionmentioning
confidence: 80%
“…Millán and Casanova [ 17 ] found an overall higher parasite prevalence in feral cat samples (84%) than in Iberian lynx samples and several parasites that both felines share, which means that domestic/feral and wild cats may be an important reservoir of parasites that can affect the Iberian lynx. In fact, Nájera et al [ 35 ] reported, for the same population in study, a case of interspecific killing and partial consumption of a feral cat by an Iberian lynx individual, which evidence the disease risk and possible outbreak that this domestic/feral species can represent for the Iberian lynx, especially in small/newly reintroduced populations. With the exception of T. cati , which is more cat-specific, according to Ribas et al [ 36 ] and Olmedo et al [ 37 ], most of the parasites found in this study have low host specificity and have mutual wild carnivores’ families, which can be explained by their similar generalist diet composition.…”
Section: Discussionmentioning
confidence: 80%
“…Besides poaching, accidental poisoning (Lozano and Malo, 2012) or natural causes of death such as disease (e.g. Fromont et al, 2000) and intra-guild predation from larger carnivores (Nájera et al, 2019) are plausible explanations of the low amount of unknown mortality found in this study. A temporally and spatially detailed GPS tracking with mortality sensors and immediate autopsy once death is confirmed would be able to shed more light on unknown and hidden mortality causes.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, FeLV primo-vaccinations and boosters were administered to wild-born lynxes during the trapping season. This may explain the low contact rates with this agent in the reintroduced population at all reintroduction/study sites, even after contact with currently infected domestic cats during intraguild predations [ 44 ]. Only one juvenile wild-born lynx found dead was FeLV provirus-positive and coinfected with SuHV-1.…”
Section: Discussionmentioning
confidence: 99%
“…We may find higher CDV prevalence than in the former studies, since the reintroduction landscape was free from apex predators for decades, and under that scenario, meso-carnivores thrive, along with multi-host pathogens; higher lynx meso-predator contact rates may occur when the reintroduction begins [ 6 ]. During an ecological study in MRV, where changes in the carnivore community were examined before and after the Iberian lynx reintroduction, seventeen intraguild predations were detected [ 6 , 44 ]. These interactions well-provided the arena for the direct transmission of pathogens such as CDV.…”
Section: Discussionmentioning
confidence: 99%